The Influence of Site Quality and Trust on Repurchase Interest of Tokopedia through Perceived Usefulness - Rully Restiningrum; Nurul Aini; Joko Suyono; Damarsari Ratnasahara (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: this study aims to examine the relationship between site quality variables and trust in Tokopedia consumer repurchase interest in Surabaya through the mediating variable of perceived usefulness. Design/methodology/approach: This is a quantitative study and the data will be analysed through partial Least Square (PLS). Findings: 5 out of 7 hypotheses cannot be proved and supported by this study Research limitations/implications: The respondent of this study are 95 Tokopedia user. Practical implications: Only 2 out of 7 hypotheses can be proved and supported. Paper type: This study is categorised as a case study.